Pre-operative evaluation and mid-term outcomes of anomalous origin of the left coronary artery from the pulmonary artery based on left ventricular ejection fraction - Xia, Shu-Liang; Tao, Hui-Kang; Ma, Li; Cui, Yan-Qing; Zou, Ming-Hui; Li, Jian-Ru; Li, Feng-xiang; Li, Jia; Zhang, Xu; Chen, Xin-Xin (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE:The purpose of this study was to evaluate the prognosis of patients with anomalous left coronary artery originating from pulmonary artery with varying cardiac function after surgical correction. METHODS:This was a single-center retrospective cohort study including 51 patients with anomalous left coronary artery originating from pulmonary artery, all of whom underwent surgery at our center. RESULTS: All 5 deaths occurred in the preoperative low cardiac function group (n=39). After corrected by body surface area, parameters such as left coronary artery, right coronary artery, left atrial diameter, left ventricular end-diastolic diameter, left ventricular end-systolic diameter, and main pulmonary artery diameter, were lower in patients in the normal cardiac function group than in the low cardiac function group. The proportion of Changes of T wave was higher in the low cardiac function group (P=0.005), and the duration of vasoactive drugs (dobutamine, milrinone, epinephrine, nitroglycerin.) was longer in the low cardiac function group. Left ventricular end-diastolic diameter, left ventricular end-systolic diameter, main pulmonary artery diameter, and left atrial diameter were smaller than those preoperatively (P<0.05). Left ventricular ejection fraction was higher than that preoperatively (P=0.003). The degree of mitral regurgitation in the low cardiac function group was reduced postoperatively (P<0.001). CONCLUSION: There was a significant difference between the preoperative baseline data of the low cardiac function group and the normal cardiac function group. After surgical repair, cardiac function gradually returned to normal in the low cardiac function group. The low cardiac function group required vasoactive drugs for a longer period of time. The left ventricular end-diastolic diameter, left ventricular end-systolic diameter, left atrial diameter, and main pulmonary artery diameter decreased and gradually returned to normal after surgery. The degree of mitral regurgitation in the low cardiac function group was reduced after surgery.